Protection of homologous and heterologous boosters after primary schemes of rAd26-rAd5, ChAdOx1 nCoV-19 and BBIBP-CorV during the omicron outbreak in adults of 50 years and older in Argentina: a test-negative case-control studyResearch in context - Soledad González; Santiago Olszevicki; Alejandra Gaiano; Martín Salazar; Lorena Regairaz; Ana Nina Varela Baino; Erika Bartel; Teresa Varela; Veronica V. González Martínez; Santiago Pesci; Lupe Marín; Juan Ignacio Irassar; et al. (Elsevier, 2023)
Summary: Background: After primary vaccination schemes with rAd26-rAd5 (Sputnik V), ChAdOx1 nCoV-19, BBIBP-CorV or heterologous combinations, the effectiveness of homologous or heterologous boosters (Sputnik V, ChAdOx, Pfizer-BioNTech, Moderna) against SARS-CoV-2 infections, hospitalisations and deaths has been scarcely studied. Methods: Test-negative, case-control study, conducted in Argentina during omicron BA.1 predominance, in adults ≥50 years old tested for SARS-CoV-2 who had received two or three doses of COVID-19 vaccines. Outcomes were COVID-associated infections, hospitalisations and deaths after administering mRNA and vectored boosters, < or ≥60 days from the last dose. Findings: Of 422,124 individuals tested for SARS-CoV-2, 221,993 (52.5%) tested positive; 190,884 (45.2%) and 231,260 (54.8%) had received 2-dose and 3-dose vaccination schemes, respectively. The 3-dose scheme reduced infections, hospitalisations and death (OR 0.81 [0.80-0.83]; 0.28 [0.25-0.32] and 0.25 [0.22-0.28] respectively), but protection dropped after 60 days to 1.04 [1.01-1.06]; 0.52 [0.44-0.61] and 0.38 [0.33-0.45]). Compared with 2-dose-schemes, homologous boosters after primary schemes with vectored-vaccines provided lower protection against infections < and ≥60 days (0.94 [0.92-0.97] and 1.05 [1.01-1.09], respectively) but protected against hospitalisations (0.30 [0.26-0.35]) and deaths (0.29 [0.25-0.33]), decreasing after 60 days (0.59 [0.47-0.74] and 0.51 [0.41-0.64], respectively). Heterologous boosters protected against infections (0.70 [0.68-0.71]) but decreased after 60 days (1.01 [0.98-1.04]) and against hospitalisations and deaths (0.26 [0.22-0.31] and 0.22 [0.18-0.25], respectively), which also decreased after 60 days (0.43 [0.35-0.53] and 0.33 [0.26-0.41], respectively). Heterologous boosters protected against infections when applied <60 days (0.70 [0.68-0.71], p < 0.001), against hospitalisations when applied ≥60 days (0.43 [0.35-0.53], p < 0.01), and against deaths < and ≥60 days (0.22 [0.18-0.25], p < 0.01 and 0.33 [0.26-0.41], p < 0.001). Interpretation: During omicron predominance, heterologous boosters such as viral vectored and mRNA vaccines, following Sputnik V, ChAdOx1, Sinopharm or heterologous primary schemes might provide better protection against death; this effect might last longer in individuals aged ≥50 than homologous boosters. Funding: None.